2017
DOI: 10.1097/prs.0000000000003748
|View full text |Cite|
|
Sign up to set email alerts
|

Direct-to-Implant versus Two-Stage Tissue Expander/Implant Reconstruction: 2-Year Risks and Patient-Reported Outcomes from a Prospective, Multicenter Study

Abstract: Background Direct-to-implant breast reconstruction offers time-saving advantages over two-stage techniques. However, use of direct-to-implant reconstruction remains limited, in part, because of concerns over complication rates.1,2 The authors’ aim was to compare 2-year complications and patient-reported outcomes for direct-to-implant versus tissue expander/implant reconstruction. Methods Patients undergoing immediate direct-to-implant or tissue expander/implant reconstruction were enrolled in the Mastectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 21 publications
1
48
2
Order By: Relevance
“…Increased numbers of re-operations could reflect more aggressive management of complications when mesh is used, but the use of mesh does not seem to translate into a reduced percentage of implant loss. Although the proportions of patients with implant loss and return to theatre in this study are much lower than those reported in a 2017 randomised trial,11, 13 they are much higher than those reported in other large prospective observational studies14, 15, 28 and summarised in recent systematic reviews 8, 9. This large, multicentre study is likely to reflect real-world outcomes of immediate implant-based breast reconstruction, and highlights the need for improvement in this area.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Increased numbers of re-operations could reflect more aggressive management of complications when mesh is used, but the use of mesh does not seem to translate into a reduced percentage of implant loss. Although the proportions of patients with implant loss and return to theatre in this study are much lower than those reported in a 2017 randomised trial,11, 13 they are much higher than those reported in other large prospective observational studies14, 15, 28 and summarised in recent systematic reviews 8, 9. This large, multicentre study is likely to reflect real-world outcomes of immediate implant-based breast reconstruction, and highlights the need for improvement in this area.…”
Section: Discussioncontrasting
confidence: 51%
“…The study was criticised because the participating surgeons had limited experience with the technique, 12 but further analysis did not identify a learning curve effect 13 . However, other large multicentre prospective studies have not shown a significant difference in incidence of complications or patient-reported outcomes between single-stage direct-to-implant and two-stage techniques, 14 or between two-stage expander-implant reconstruction done with and without acellular dermal matrix 15 . Although these findings are supportive of the technique, there remains the need for high-quality evidence from a randomised study to support practice.…”
Section: Introductionmentioning
confidence: 99%
“…One-year risk of complications in our cohort are comparable to other long-term follow-up values reported in the literature (Table 2). 2326,5052 Although these rates are useful as benchmark figures for the population, they have limited utility as risk estimates for most individual patients. That is, the mean incidence of a complication is not representative of most patients, because the distribution of risk is so positively skewed (skewness = 2.027, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A strength of this approach is the ability to complete the reconstruction in a single-stage, while maintaining similar rates of revision and complications as well as patient-reported outcomes compared with tissue expander/implant reconstruction. 13 , 14 Optimal candidates for DP-DTI reconstruction are patients with relatively smaller breasts who wish to maintain the same size. 10 , 15 In addition, it is best performed in patients who demonstrate well-perfused mastectomy flaps because ADM is fundamentally a graft that relies on revascularization by the overlying tissues.…”
Section: Description Of Most-effective Proceduresmentioning
confidence: 99%